Process for plating high-strength structural steel with low-hydrogen brittleness zinc-nickel alloy and plating layer structure
By using a titanium alloy plating process on high-strength structural steel, the high pollution problem of the cadmium-titanium alloy plating process on high-strength structural steel was solved, the current efficiency of the plating solution was improved, a low hydrogen embrittlement coating was prepared, and the durability of the coating was enhanced.
Patent Information
- Application Number
- CN202511221340.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-12-19
AI Technical Summary
Existing processes for cadmium-titanium alloy plating on high-strength structural steel in the aerospace field suffer from high pollution and low current efficiency in the plating solution, making it difficult to prepare coatings with low hydrogen embrittlement.
The process of plating high-strength structural steel with low-hydrogen brittle zinc-nickel alloy involves pretreatment of the high-strength structural steel workpiece, plating with cobalt-titanium alloy, plating with zinc-nickel alloy, and passivation with hexavalent chromium. The cobalt-titanium alloy coating blocks the diffusion of hydrogen into the substrate, and a high-current-efficiency plating solution and passivation process are used.
The preparation of low hydrogen embrittlement coatings was achieved, improving the electrical conductivity and current efficiency of the plating solution, enhancing the durability of the coating and the plating solution, and solving the hydrogen durability problem.
Smart Images

Figure CN121161379A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of metal surface treatment, and particularly relates to a high-strength structural steel plating low-hydrogen brittle zinc-nickel alloy process and plated layer structure. BACKGROUND
[0002] With the rapid development of China's aerospace industry, high-strength structural steel materials are widely used in the aviation industry to manufacture parts. Currently, cadmium-titanium alloy plating process is used to prepare protective layers for high-strength structural steel parts. Test research on electroplating cadmium-titanium alloy on A100 steel parts shows that most of the hydrogen in the cadmium-titanium alloy sample exists in the plated layer, and only a small amount penetrates into the substrate [1] . It is generally believed that titanium in the cadmium-titanium alloy coating can combine with hydrogen to form titanium trihydride compounds, effectively preventing the penetration of hydrogen elements into the high-strength structural steel substrate.
[0003] Electroplating cadmium-titanium alloy has high pollution problems, which is harmful to the environment and does not meet China's green development policy. The aerospace field is actively developing zinc-nickel alloy plating process to replace the highly toxic cadmium plating process, and has achieved good environmental benefits [2] . On this basis, developing a zinc-nickel alloy plating process to replace cadmium-titanium alloy plating will become a research hotspot in the industry.
[0004] The invention patent application "High-strength structural steel cyanide-free cadmium-iron alloy plating process" with the application publication number CN 119980226 A discloses a new technology of sequentially plating nickel-titanium alloy, cadmium-iron alloy, and hexavalent chromium passivation on a high-strength steel substrate, which attempts to replace the current cadmium-titanium alloy plating process with this technical solution. However, the nickel-titanium alloy plating solution contains citrate with high coordination ability, which results in low current efficiency of the plating solution and large amount of hydrogen evolution, which is not conducive to the preparation of low-hydrogen brittle plated layer structure.
[0005] Reference: [1]. Yu Bo, Tang Zhineng, Peng Chao, et al. Influence of cyanide-free electroplating cadmium-titanium alloy on hydrogen embrittlement performance of steel substrate [J]. Electroplating and Finishing, 2011, 33(11): 1-4. [2]. Qin Zhili, Guo Chongwu, High corrosion resistance zinc-nickel alloy protective layer in aerospace field [J]. Electroplating and Finishing, 2023, 42(9): 14-17. SUMMARY
[0006] To solve the high pollution problem of cadmium-titanium alloy plating on high-strength structural steel in the aerospace field, the present application provides a high-strength structural steel plating low-hydrogen brittle zinc-nickel alloy process. In order to achieve the above purpose, the present application adopts the following technical scheme: A high-strength structural steel plating low-hydrogen brittle zinc-nickel alloy process, comprising the following process: (1) High-strength structural steel workpiece pretreatment, including oil removal and sulfuric acid anodic activation; (2) High-strength structural steel workpiece is treated before plating with cobalt-titanium alloy process to prepare cobalt-titanium alloy plating layer; (3) High-strength structural steel workpiece is plated with cobalt-titanium alloy, and then plated with zinc-nickel alloy process to prepare zinc-nickel alloy plating layer; (4) High-strength structural steel workpiece is plated with zinc-nickel alloy, and then subjected to hydrogen removal treatment; (5) High-strength structural steel workpiece is subjected to hydrogen removal, and then prepared with hexavalent chromium passivation process to prepare hexavalent chromium passivation film; The cobalt-titanium alloy plating process comprises the following components and process parameters: Cobalt sulfate heptahydrate 160-200 g / L, potassium fluorotitanate 8-12 g / L, sodium fluoride 2-8 g / L, sodium sulfate 80-120 g / L, sodium hydrogen succinate 30-50 g / L, walking agent 8-12 mL / L, wetting agent 1-3 mL / L, plating solution pH value 3.8-4.4, plating bath temperature 20-35 ℃, cathode current density 1-2 A / dm 2 , cathode moving speed 4-6 m / min; The walking agent comprises 20-30 g / L of condensation reaction product of salicylic acid and epichlorohydrin, 80-120 g / L of sodium saccharin, 200-300 mL / L of 35% sodium allylsulfonate, and 140-160 mL / L of ethanol; The wetting agent comprises 20-40 g / L of sodium ethylhexylsulfonate.
[0007] In some embodiments, the walking agent is prepared as follows: Half of the required amount of water is added to a reaction tank, and then ethanol is added according to the process formula, followed by the addition of the condensation reaction product of salicylic acid and epichlorohydrin, stirring, the addition of sodium saccharin and 35% sodium allylsulfonate according to the process formula, stirring until the sodium saccharin is completely dissolved, and then the addition of pure water to the required volume.
[0008] In some embodiments, cobalt particles are used as anodes, the cobalt particles are loaded into a titanium anode basket, an anode bag is sleeved on the anode basket, and the area ratio of the anode to the cathode is 4:(0.5-1.5).
[0009] In some embodiments, solid potassium fluorotitanate is added to the plating solution during production to maintain the mass concentration of the potassium fluorotitanate within the range required by the process.
[0010] In some embodiments, the process components and parameters of the sulfuric acid anode activation are as follows: Sulfuric acid 200-300 g / L, normal temperature operation, the workpiece to be plated is used as an anode, anode current density 0.6-1.2 A / dm 2 , electrolysis time 20-40 s.
[0011] In some of the embodiments, the zinc nickel alloy plating process employs DETRONZIN 1215 Base zinc nickel alloy electroplating process: Zinc 5.5-8.5 g / L, Nickel 1.0-1.8 g / L, Sodium hydroxide 120-135 g / L, DETRONZIN 1215 Base Additive 90-110 mL / L, DETRONZIN 1215 Brightener Primary Brightener 1.0-5.0 mL / L, DETRONZIN 1215 Purifier R Purifier 0.1-0.8 mL / L, Bath temperature 21-28 °C, Cathodic current density 1.0-3.0 A / dm 2 , Cathodic movement 4-6 m / min.
[0012] In some of the embodiments, the zinc nickel alloy plating process employs DETRONZIN 1377 Acid zinc nickel alloy electroplating process: Zinc 22-30 g / L, Nickel 22-30 g / L, Potassium chloride 160-190 g / L, Ammonium chloride 45-75 g / L, DETRONZIN 1377 A Base Additive 10-20 mL / L, DETRONZIN 1377 B Brightener Primary Brightener 0.5-1.5 mL / L, DETRONZIN 1377 C Complex Complexing Agent 10-20 mL / L, DETRONZIN 1377 D Additive Additive 8-12 mL / L, Bath temperature 27-31 °C, Bath pH 4.6-5.2, Cathodic current density 0.5-3.5 A / dm 2 , Cathodic movement 3-5 m / min.
[0013] In some of the embodiments, the hexavalent chromium passivation process employs CB 380 Hexavalent chromium color passivation process: CB 380 Zinc nickel hexavalent chromium color passivation agent 80-100 mL / L, Passivation bath pH 1.6-1.8, Operating temperature 35-40 °C, Immersion time 60-80 s, Workpiece oscillation.
[0014] In some of the embodiments, the hexavalent chromium passivation process employs UUC 730 Hexavalent chromium black passivation process: UUC 730 A Additive 120-160 mL / L, UUC 730 B Additive 120-160 mL / L, Passivation temperature 20-30 °C, Passivation bath pH 0.7-0.9, Passivation time 60-120 s, Workpiece oscillation.
[0015] The high-strength structural steel low-hydrogen embrittlement zinc-nickel alloy plating structure comprises a high-strength structural steel base body, and a cobalt-titanium alloy plating layer, a zinc-nickel alloy plating layer and a hexavalent chromium passivation film prepared on the high-strength structural steel base body in sequence.
[0016] In some embodiments, the thickness of the cobalt-titanium alloy plating layer is 4-8 microns.
[0017] In some embodiments, the thickness of the zinc-nickel alloy plating layer is 5-20 microns.
[0018] The titanium element in the cobalt-titanium alloy plating layer has the characteristic of blocking the diffusion of hydrogen element to the high-strength structural steel base body, so the cobalt-titanium alloy plating layer is prepared on the high-strength structural steel base body first, and then the zinc-nickel alloy plating layer is prepared, in the electroplating process, the cobalt-titanium alloy plating layer can block the penetration of hydrogen element into the base body, avoiding the hydrogen embrittlement of the high-strength steel base body.
[0019] Compared with the prior art, the present application has the following beneficial effects: 1. The high-strength structural steel low-hydrogen embrittlement zinc-nickel alloy plating process disclosed by the present application does not contain high-coordination ability complexing agent in the cobalt-titanium alloy plating solution, the plating solution has high current efficiency, and the hydrogen evolution is extremely small in the process of plating cobalt-titanium alloy, which is beneficial to the preparation of low-hydrogen embrittlement plating layer. 2. The high-strength structural steel low-hydrogen embrittlement zinc-nickel alloy plating process disclosed by the present application plates cobalt-titanium alloy on the high-strength structural steel base body, the titanium atoms in the cobalt-titanium alloy plating layer can react with hydrogen atoms to generate titanium trihydride compound, thereby effectively preventing the diffusion of hydrogen element to the base body direction and avoiding the hydrogen embrittlement of the high-strength structural steel base body. 3. The high-strength structural steel low-hydrogen embrittlement zinc-nickel alloy plating process disclosed by the present application plates zinc-nickel alloy after plating cobalt-titanium alloy on the high-strength structural steel base body, the cobalt-titanium alloy plating layer can effectively prevent the diffusion of hydrogen element to the base body direction. BRIEF DESCRIPTION OF DRAWINGS
[0020] The drawings described herein are used to provide further understanding of the present application, constitute a part of the present application, and do not constitute improper limitation on the present application. In the drawings: Figure 1 is the schematic diagram of the plating layer structure prepared by example 1, example 2, example 3 and example 4 of the present application; Figure 2 is the photo of the high-strength steel zinc-nickel alloy black passivation test piece after neutral salt spray test. DETAILED DESCRIPTION
[0021] The present application will be described in detail below in combination with the drawings and specific embodiments, and the schematic embodiments and descriptions of the present application are used to explain the present application, but do not constitute limitation on the present application.
[0022] A process for plating low-hydrogen brittle zinc-nickel alloy on high-strength structural steel, comprising pretreatment of high-strength structural steel and sequentially preparing a cobalt-titanium alloy plating layer, a zinc-nickel alloy plating layer and a passivation film on the high-strength structural steel substrate from inside to outside.
[0023] The surface of the high-strength structural steel workpiece substrate is subjected to oil removal and sulfuric acid anodic electrolytic activation.
[0024] Preferably, the process components and parameters for the sulfuric acid anodic activation are as follows: Sulfuric acid 200-300 g / L, normal temperature operation, the workpiece to be plated as anode, anode current density 0.6-1.2 A / dm 2 , electrolysis 20-40 s.
[0025] The high-strength structural steel workpiece after pretreatment is subjected to the cobalt-titanium alloy plating process of the present application to prepare a cobalt-titanium alloy plating layer, preferably the thickness of the cobalt-titanium alloy plating layer is 4-8 μm.
[0026] Cobalt sulfate heptahydrate 160-200 g / L, potassium fluotitanate 8-12 g / L, sodium fluoride 2-8 g / L, sodium sulfate 80-120 g / L, sodium hydrogen succinate 30-50 g / L, running agent 8-12 mL / L, wetting agent 1-3 mL / L, plating bath pH value 3.8-4.4, plating bath temperature 20-35 ℃, cathode current density 1-2 A / dm 2 , cathode moving speed 4-6 m / min.
[0027] Preferably, the running agent comprises 20-30 g / L of condensation reaction product of salicylic acid and epichlorohydrin, 80-120 g / L of sodium saccharin, 200-300 mL / L of 35% sodium allylsulfonate and 140-160 mL / L of ethanol.
[0028] Preferably, half of the required amount of water is added to the reaction tank, the ethanol and the condensation reaction product of salicylic acid and epichlorohydrin are added according to the process formula, the sodium saccharin and the 35% sodium allylsulfonate are added according to the process formula, the sodium saccharin is stirred until it is completely dissolved, and then pure water is added to the required volume.
[0029] Preferably, the wetting agent comprises 20-40 g / L of sodium ethylhexylsulfonate.
[0030] Preferably, cobalt particles are used as anode, the cobalt particles are loaded into a titanium anode basket, an anode bag is used to cover the anode basket, and the area ratio of the anode to the cathode is 4:(0.5-1.5).
[0031] Preferably, solid potassium fluotitanate is added to the plating bath during production to keep the mass concentration of the potassium fluotitanate within the range required by the process.
[0032] The high-strength structural steel workpiece plated with cobalt-titanium alloy is plated with zinc-nickel alloy by using the current zinc-nickel alloy plating process, preferably, the thickness of the zinc-nickel alloy plating layer is 5-20 μm.
[0033] Preferably, the zinc-nickel alloy plating layer is prepared by using Detronzin 1215 basic zinc-nickel alloy electroplating process of Superbond Chemicals: Zinc 5.5-8.5 g / L, nickel 1.0-1.8 g / L, sodium hydroxide 120-135 g / L, DETRONZIN 1215 Base auxiliary agent 90-110 mL / L, DETRONZIN 1215 Brightener main brightener 1.0-5.0 mL / L, DETRONZIN 1215 Purifier R purifier 0.1-0.8 mL / L, plating bath temperature 21-28 ℃, cathode current density 1.0-3.0 A / dm 2 , cathode moving speed 4-6 m / min; Preferably, the zinc-nickel alloy plating layer is prepared by using DETRONZIN 1377 acid zinc-nickel alloy electroplating process of Superbond Chemicals: Zinc 22-30 g / L, nickel 22-30 g / L, potassium chloride 160-190 g / L, ammonium chloride 45-75 g / L, DETRONZIN 1377A Base auxiliary agent 10-20 mL / L, DETRONZIN 1377B Bri main brightener 0.5-1.5 mL / L, DETRONZIN 1377C Complex complexing agent 10-20 mL / L, DETRONZIN 1377D Additive additive 8-12 mL / L, plating bath temperature 27-31 ℃, plating solution pH value 4.6-5.2, cathode current density 0.5-3.5 A / dm 2 , cathode moving speed 3-5 m / min.
[0034] The high-strength structural steel workpiece plated with zinc-nickel alloy is subjected to hydrogen removal treatment: the plated workpiece is subjected to hydrogen removal at 190-210 ℃ for 10-24 h.
[0035] The high-strength structural steel workpiece after hydrogen removal is subjected to passivation film preparation by using the current hexavalent passivation process.
[0036] Preferably, the passivation film is prepared by using CB 380 hexavalent chromium color passivation process of Superbond Chemicals: CB 380 zinc-nickel hexavalent chromium color passivation agent 80-100 mL / L, passivation solution pH value 1.6-1.8, operation temperature 35-40 ℃, immersion time 60-80 s, workpiece swinging.
[0037] Preferably, the passivation film is prepared by using UUC 730 hexavalent chromium black passivation process of Superbond Chemicals: UUC 730 A additive 120~160mL / L, UUC 730 B additive 120~160mL / L, passivation temperature 20~30℃, passivation solution pH 0.7~0.9, passivation time 60~120s.
[0038] Preferably, the specific process of the passivation process is as follows: "removal of film with 1% sulfuric acid by volume → water washing → passivation → water washing → removal from the tank → blowing away residual water droplets on the surface of the plated part with high-pressure air".
[0039] After passivation, high-strength structural steel workpieces are dried at 55-60℃ for 10-15 minutes.
[0040] Example 1: like Figure 1 As shown, a process and coating structure for plating a high-strength structural steel with a low-hydrogen embrittlement zinc-nickel alloy includes a pretreatment of a high-strength structural steel substrate 1, and the sequential preparation of a cobalt-titanium alloy coating 2, a zinc-nickel alloy coating 3, and a hexavalent chromium colored passivation film 4 on the high-strength structural steel substrate 1 from the inside out.
[0041] 1. Pre-processing: The high-strength structural steel workpiece substrate 1 is subjected to the following process: "alkaline chemical degreasing → water washing → alkaline anodic electrolytic degreasing → water washing → sulfuric acid anodic electrolytic activation → water washing".
[0042] The sulfuric acid anodic electrolytic activation adopts the following anodic electrolytic activation process: Sulfuric acid 250g / L, room temperature operation, with the workpiece to be plated as the anode, anolyte current density 1A / dm³ 2 Electrolysis for 30 seconds.
[0043] 2. Cobalt-plated titanium alloy: After pretreatment of the high-strength structural steel workpiece, a cobalt-titanium alloy coating 2 is prepared using the cobalt-titanium alloy plating process of the present invention, with a coating thickness of 6μm.
[0044] 1) Preparation of the positioning agent: The positioning agent comprises 25 g / L of the condensation reaction product of salicylic acid and epichlorohydrin, 100 g / L of sodium saccharin, 250 mL / L of sodium propylene sulfonate with a mass fraction of 35%, and 150 mL / L of ethanol.
[0045] Add half the required amount of pure water to the reaction vessel. Add ethanol and the condensation reaction product of salicylic acid and epichlorohydrin according to the process formula. Stir evenly. Add sodium saccharin and sodium propylene sulfonate (35% by mass) according to the process formula. Stir until the sodium saccharin dissolves. Then add pure water to the required volume.
[0046] 2) Cobalt-plated titanium alloy: Cobalt sulfate heptahydrate 180 g / L, potassium fluotitanate 10 g / L, sodium fluoride 5 g / L, sodium sulfate 100 g / L, sodium hydrogen succinate 40 g / L, leveler 10 mL / L, wetting agent 2 mL / L, pH of plating solution 4.1, temperature of plating bath 25 °C, cathode current density 1.5 A / dm 2 , cathode movement 5 m / min.
[0047] The wetting agent comprises sodium ethylhexyl sulfonate 30 g / L.
[0048] 3. Galvanizing nickel alloy: The high-strength structural steel workpiece is plated with cobalt-titanium alloy, and then a Detronzin 1215 alkaline zinc-nickel alloy electroplating process is used to prepare a zinc-nickel alloy plating layer 3 with a thickness of 12 μm.
[0049] Zinc 7 g / L, nickel 1.4 g / L, sodium hydroxide 128 g / L, DETRONZIN 1215 Base auxiliary agent 100 mL / L, DETRONZIN 1215 Brightener main brightener 3 mL / L, DETRONZIN 1215 Purifier R purifier 0.5 mL / L, temperature of plating bath 25 °C, cathode current density 2 A / dm 2 , cathode movement 5 m / min.
[0050] 4. Hydrogen removal: The high-strength structural steel workpiece is plated with zinc-nickel alloy, and then hydrogen is removed at 200 °C for 20 h.
[0051] 5. Passivation: The high-strength structural steel workpiece is passivated after hydrogen removal using a CB 380 hexavalent chromium color passivation process of Superbond Technology to prepare a hexavalent chromium color passivation film 4.
[0052] CB 380 zinc-nickel hexavalent chromium color passivation agent 90 mL / L, pH of passivation solution 1.7, operating temperature 38 °C, immersion time 70 s, workpiece oscillation.
[0053] The specific process is "1% sulfuric acid light → water washing → passivation → water washing → out of the tank → blowing off the water droplets remaining on the surface of the workpiece with high-pressure air".
[0054] 6. Drying: The high-strength structural steel workpiece is dried at 60 °C for 10 min after passivation.
[0055] Example 2: As Figure 1As shown, a high-strength structural steel is plated with a low-hydrogen brittle zinc-nickel alloy process and plated layer structure, including high-strength structural steel substrate 1 pretreatment, and on the high-strength structural steel substrate 1 from inside to outside sequentially prepared cobalt-titanium alloy plating layer 2, zinc-nickel alloy plating layer 3, and hexavalent chromium black passivation film 4.
[0056] 1. Pretreatment: The high-strength structural steel workpiece substrate 1 is subjected to "alkaline chemical degreasing → water washing → alkaline anodic electrolytic degreasing → water washing → sulfuric acid anodic electrolytic activation → water washing".
[0057] The sulfuric acid anodic electrolytic activation adopts the following anodic electrolytic activation process: Sulfuric acid 300g / L, normal temperature operation, using the plated workpiece as an anode, anodic current density 0.6A / dm 2 , electrolysis 30s.
[0058] 2. Plating cobalt-titanium alloy: After the high-strength structural steel workpiece is pretreated, the cobalt-titanium alloy plating layer 2 is prepared by the cobalt-titanium alloy plating process of the present application, and the plating layer thickness is 6μm.
[0059] 1) Preparation of walking agent: The walking agent includes 25g / L of condensation reaction product of salicylic acid and epichlorohydrin, 100g / L of sodium saccharin, 250mL / L of 35% mass fraction sodium allylsulfonate, and 150mL / L of ethanol.
[0060] According to 1 / 2 of the required water amount, pure water is added to the reaction tank, and according to the process formula requirements, ethanol and the condensation reaction product of salicylic acid and epichlorohydrin are added, stirred uniformly, and according to the process formula requirements, sodium saccharin and 35% mass fraction sodium allylsulfonate are added, stirred until the sodium saccharin is dissolved, and then pure water is added to the required volume.
[0061] 2) Plating cobalt-titanium alloy: Cobalt sulfate heptahydrate 200g / L, potassium fluorotitanate 12g / L, sodium fluoride 8g / L, sodium sulfate 120g / L, sodium hydrogen succinate 50g / L, walking agent 10mL / L, wetting agent 2mL / L, plating solution pH 4.4, plating bath temperature 20℃, cathode current density 1.5A / dm 2 , cathode moving speed 5m / min.
[0062] The wetting agent contains 30g / L of sodium ethylhexyl sulfonate.
[0063] 3. Plating zinc-nickel alloy: After the high-strength structural steel workpiece is plated with cobalt-titanium alloy, the zinc-nickel alloy plating layer 3 is prepared by the super-bonding DETRONZIN 1377 acid zinc-nickel alloy electroplating process, and the plating layer thickness is 12μm.
[0064] Zinc 26 g / L, nickel 26 g / L, potassium chloride 175 g / L, ammonium chloride 60 g / L, DETRONZIN 1377A Base adjuvant 15 mL / L, DETRONZIN 1377B Bri main light agent 1 mL / L, DETRONZIN 1377C Complex complexing agent 15 mL / L, DETRONZIN 1377D Additive additive 10 mL / L, plating bath temperature 29°C, plating bath pH 4.9, cathode current density 2 A / dm 2 , cathode moving speed 4 m / min.
[0065] 4. Hydrogen removal: The high-strength structural steel workpiece plated with zinc-nickel alloy is subjected to hydrogen removal at 200°C for 20 h.
[0066] 5. Passivation: The high-strength structural steel workpiece after hydrogen removal is subjected to black passivation film preparation by UUC 730 hexavalent chromium black passivation process of Superbang Chemicals.
[0067] UUC 730 A additive 140 mL / L, UUC 730 B additive 140 mL / L, passivation temperature 25°C, passivation bath pH 0.8, passivation time 90 s.
[0068] The specific process is "1% sulfuric acid light-out → water washing → passivation → water washing → tank-out → blowing off the water droplets remaining on the surface of the plated workpiece by high-pressure air".
[0069] 6. Drying: The high-strength structural steel workpiece after passivation is dried at 60°C for 10 min.
[0070] Example 3: As shown in Figure 1 , a high-strength structural steel plating low-hydrogen brittle zinc-nickel alloy process and plated layer structure, comprising high-strength structural steel substrate 1 pretreatment, and on the high-strength structural steel substrate 1 from inside to outside sequentially prepared cobalt-titanium alloy plated layer 2, zinc-nickel alloy plated layer 3, and hexavalent chromium color passivation film 4.
[0071] 1. Pretreatment: The high-strength structural steel workpiece substrate 1 is subjected to "alkaline chemical degreasing → water washing → alkaline anodic electrolytic degreasing → water washing → sulfuric acid anodic electrolytic activation → water washing".
[0072] The sulfuric acid anodic electrolytic activation adopts the following anodic electrolytic activation process: Sulfuric acid 200 g / L, normal temperature operation, using the plated workpiece as anode, anode current density 1.2 A / dm 2 , electrolysis time 30 s.
[0073] 2. Cobalt-titanium alloy plating: The high-strength structural steel workpiece is pre-processed, and then a cobalt-titanium alloy plating process of the application is used to prepare a cobalt-titanium alloy plating layer 2 with a plating layer thickness of 6 μm.
[0074] 1) Preparation of a walking agent: The walking agent comprises 25 g / L of a condensation reaction product of salicylic acid and epichlorohydrin, 100 g / L of sodium saccharin, 250 mL / L of sodium allylsulfonate with a mass fraction of 35%, and 150 mL / L of ethanol.
[0075] Half of the required amount of water is added to the reaction tank, and then ethanol and the condensation reaction product of salicylic acid and epichlorohydrin are added according to the process formula, and stirred uniformly. Then, sodium saccharin and sodium allylsulfonate with a mass fraction of 35% are added according to the process formula, and stirred until the sodium saccharin is completely dissolved. Then, pure water is added to the required volume.
[0076] 2) Cobalt-titanium alloy plating: Cobalt sulfate heptahydrate 160 g / L, potassium fluorotitanate 8 g / L, sodium fluoride 2 g / L, sodium sulfate 80 g / L, sodium hydrogen succinate 30 g / L, walking agent 10 mL / L, wetting agent 2 mL / L, plating solution pH 3.8, plating bath temperature 35°C, cathode current density 0.8 A / dm 2 , cathode moving speed 5 m / min.
[0077] The wetting agent comprises sodium ethylhexylsulfonate 30 g / L.
[0078] 3) Zinc-nickel alloy plating: After the high-strength structural steel workpiece is plated with cobalt-titanium alloy, the Detronzin 1215 alkaline zinc-nickel alloy electroplating process of Superbond is used to prepare a zinc-nickel alloy plating layer 3 with a plating layer thickness of 12 μm.
[0079] Zinc 8.5 g / L, nickel 1.8 g / L, sodium hydroxide 135 g / L, DETRONZIN 1215 Base auxiliary agent 100 mL / L, DETRONZIN 1215 Brightener main brightener 3 mL / L, DETRONZIN 1215 Purifier R purifier 0.5 mL / L, plating bath temperature 21°C, cathode current density 2 A / dm 2 , cathode moving speed 5 m / min.
[0080] 4) Hydrogen removal: After the high-strength structural steel workpiece is plated with zinc-nickel alloy, hydrogen removal is performed at 200°C for 20 h.
[0081] 5) Passivation: After the high-strength structural steel workpiece is hydrogen-removed, the CB 380 hexavalent chromium color passivation process of Superbond is used to prepare a hexavalent chromium color passivation film 4.
[0082] CB 380 zinc-nickel hexavalent chromium colored passivating agent 100mL / L, passivation solution pH 1.8, operating temperature 38℃, immersion time 70s, workpiece oscillation.
[0083] The specific process is as follows: "1% sulfuric acid brightening → water washing → passivation → water washing → removal from the tank → blowing away residual water droplets on the surface of the plated parts with high-pressure air".
[0084] 6. Drying: After passivation, the high-strength structural steel workpiece is dried at 60℃ for 10 minutes. Example
[0085] like Figure 1 As shown, a process and coating structure for plating a high-strength structural steel with a low-hydrogen embrittlement zinc-nickel alloy includes a pretreatment of a high-strength structural steel substrate 1, and the sequential preparation of a cobalt-titanium alloy coating 2, a zinc-nickel alloy coating 3, and a hexavalent chromium black passivation film 4 on the high-strength structural steel substrate 1 from the inside out.
[0086] 1. Pre-processing: The high-strength structural steel workpiece substrate 1 is subjected to the following process: "alkaline chemical degreasing → water washing → alkaline anodic electrolytic degreasing → water washing → sulfuric acid anodic electrolytic activation → water washing".
[0087] The sulfuric acid anodic electrolytic activation adopts the following anodic electrolytic activation process: Sulfuric acid 280 g / L, room temperature operation, with the workpiece to be plated as the anode, anolyte current density 0.8 A / dm³ 2 Electrolysis for 30 seconds.
[0088] 2. Cobalt-plated titanium alloy: After pretreatment of the high-strength structural steel workpiece, a cobalt-titanium alloy coating 2 is prepared using the cobalt-titanium alloy plating process of the present invention, with a coating thickness of 6μm.
[0089] 1) Preparation of the positioning agent: The positioning agent comprises 25 g / L of the condensation reaction product of salicylic acid and epichlorohydrin, 100 g / L of sodium saccharin, 250 mL / L of sodium propylene sulfonate with a mass fraction of 35%, and 150 mL / L of ethanol.
[0090] Add half the required amount of pure water to the reaction vessel. Add ethanol and the condensation reaction product of salicylic acid and epichlorohydrin according to the process formula. Stir evenly. Add sodium saccharin and sodium propylene sulfonate (35% by mass) according to the process formula. Stir until the sodium saccharin dissolves. Then add pure water to the required volume.
[0091] 2) Cobalt-plated titanium alloy: Cobalt sulfate heptahydrate 190 g / L, potassium fluotitanate 11 g / L, sodium fluoride 7 g / L, sodium sulfate 110 g / L, sodium hydrogen succinate 45 g / L, leveling agent 10 mL / L, wetting agent 2 mL / L, plating bath pH 4.2, plating bath temperature 25°C, cathode current density 1.2 A / dm 2 , cathode moving speed 5 m / min.
[0092] The wetting agent comprises sodium ethylhexyl sulfonate 30 g / L.
[0093] 3. Galvanizing nickel alloy: The high-strength structural steel workpiece plated with cobalt-titanium alloy is prepared with the super-bonding DETRONZIN 1377 acidic zinc-nickel alloy electroplating process to prepare a zinc-nickel alloy plating layer 3, and the plating layer thickness is 12 μm.
[0094] Zinc 30 g / L, nickel 30 g / L, potassium chloride 160 g / L, ammonium chloride 75 g / L, DETRONZIN 1377A Base auxiliary agent 15 mL / L, DETRONZIN 1377B Bri main light agent 1 mL / L, DETRONZIN 1377C Complex complexing agent 20 mL / L, DETRONZIN 1377D Additive additive 10 mL / L, plating bath temperature 27°C, plating bath pH 5, cathode current density 2 A / dm 2 , cathode moving speed 4 m / min.
[0095] 4. Hydrogen removal: The high-strength structural steel workpiece plated with zinc-nickel alloy is hydrogen-removed at 200°C for 20 h.
[0096] 5. Passivation: The high-strength structural steel workpiece after hydrogen removal is prepared with the UUC 730 hexavalent chromium black passivation process of super-bonding UUC to prepare a hexavalent chromium black passivation film 4.
[0097] UUC 730 A additive 160 mL / L, UUC 730 B additive 160 mL / L, passivation temperature 20°C, passivation bath pH 0.8, passivation time 90 s.
[0098] The specific process is "1% sulfuric acid light → water washing → passivation → water washing → out of the tank → blowing off the water droplets remaining on the surface of the plated workpiece with high-pressure air".
[0099] 6. Drying: The high-strength structural steel workpiece after passivation is dried at 60°C for 10 min.
[0100] Test Example 1: The high-strength structural steel is of type 23Co14Ni12Cr3Mo, a hydrogen embrittlement test bar is prepared according to HB 5067.1-2005 Hydrogen Embrittlement Test for Plating Processes Part 1: Mechanical Method, and a cobalt-titanium alloy plating layer and a zinc-nickel alloy plating layer are prepared on the surface of the hydrogen embrittlement test bar subjected to oil removal treatment according to the process requirements of Example 1, and then the hydrogen is removed at 200 ℃ for 24 h; the test bar is not broken after being stretched for 200 h according to the standard test of HB 5067.1-2005, and the test result meets the standard requirements.
[0101] Test Example 2: A neutral salt spray test is performed according to GB / T 10125-2021 Artificial Atmosphere Corrosion Test Salt Spray Test, and the zinc-nickel alloy color passivated sample piece of the high-strength structural steel prepared in Example 1 and Example 2 is free of white rust on the surface after 526 h, and the zinc-nickel alloy black passivated sample piece of the high-strength structural steel prepared in Example 3 and Example 4 is free of white rust on the surface after 552 h. The zinc-nickel alloy plating layer structure prepared in the application has excellent corrosion resistance.
[0102] Test Example 3: The zinc-nickel alloy sample piece of the high-strength structural steel prepared in Example 1, Example 2, Example 3 and Example 4 is subjected to a coating adhesion test according to GB / T 5270-2005 Metal Coatings on Metal Substrates Review of Test Methods for Adhesion of Electrodeposited and Chemically Deposited Coatings, and the sample piece is heated to 220 ℃ in a heating furnace for 60 min, and then taken out and quenched in water at room temperature. The coating does not appear to be blistering and peeling, and the coating adhesion is good.
[0103] Test Example 4: The zinc-nickel alloy sample piece of the high-strength structural steel prepared in Example 1, Example 2, Example 3 and Example 4 is subjected to a mold test for 28 days according to GJB 150.9A-2009 Military Equipment Laboratory Environmental Test Methods Part 10: Mold Test, and the surface of the sample piece is free of mold, which meets the requirements of the industry standard.
[0104] Test Example 5: A cadmium-titanium alloy plating solution is prepared: cobalt sulfate heptahydrate 180 g / L, potassium fluotitanate 10 g / L, sodium fluoride 5 g / L, sodium sulfate 100 g / L, hydrogen sodium succinate 40 g / L, running agent 10 mL / L, wetting agent 2 mL / L, and the pH of the plating solution is 4.1, and the temperature of the plating bath is 25 ℃. The current efficiency of the plating solution is determined by the coulometric method according to JB / T 7704.3-1995 Test Method for Electroplating Solution Cathodic Current Efficiency Test, and the cathode current density is 1.5 A / dm 2 , and the current efficiency is 99.48%.
[0105] The above describes the technical solutions provided by the embodiments of the present application in detail. The principles and implementation manners of the embodiments of the present application are described by using specific examples. The above description of the embodiments is only used to help understand the principles of the embodiments of the present application. It should be pointed out that, according to the principles and concepts of the embodiments of the present application, a plurality of modifications and improvements can be made in the specific implementation manners and application scopes by the general technical personnel in the field, and these should fall within the protection scope of the present application.
Claims
1. A process for plating high-strength structural steel with a low-hydrogen embrittlement zinc-nickel alloy, characterized in that, The process includes the following steps: (1) Pretreatment of high-strength structural steel workpieces, including degreasing and sulfuric acid anodizing; (2) After pretreatment, the high-strength structural steel workpiece is coated with a cobalt-titanium alloy by a cobalt-titanium alloy plating process. (3) After high-strength structural steel workpieces are plated with cobalt-titanium alloy, zinc-nickel alloy coating is prepared by zinc-nickel alloy plating process. (4) High-strength structural steel workpieces are subjected to hydrogen removal treatment after being plated with zinc-nickel alloy. (5) After hydrogen removal, high-strength structural steel workpieces are prepared with hexavalent chromium passivation film using a hexavalent chromium passivation process; The cobalt-titanium alloy plating process includes the following components and process parameters: Cobalt sulfate heptahydrate 160–200 g / L, potassium fluorotitanate 8–12 g / L, sodium fluoride 2–8 g / L, sodium sulfate 80–120 g / L, sodium hydrogen succinate 30–50 g / L, leveling agent 8–12 mL / L, wetting agent 1–3 mL / L, plating bath pH 3.8–4.4, plating bath temperature 20–35℃, cathode current density 1–2 A / dm³ 2 The cathode moves at a speed of 4–6 m / min. The positioning agent comprises 20-30 g / L of the condensation reaction product of salicylic acid and epichlorohydrin, 80-120 g / L of sodium saccharin, 200-300 mL / L of sodium propylene sulfonate with a mass fraction of 35%, and 140-160 mL / L of ethanol. The wetting agent contains 20-40 g / L of sodium ethylhexyl sulfonate.
2. The process for plating high-strength structural steel with a low-hydrogen embrittlement zinc-nickel alloy as described in claim 1, characterized in that, The positioning agent is prepared as follows: Add half the required amount of pure water to the reaction vessel. Add ethanol according to the process formula, then add the condensation reaction product of salicylic acid and epichlorohydrin. Stir until homogeneous. Add sodium saccharin and sodium propylene sulfonate (35% by mass) according to the process formula. Stir until the sodium saccharin is completely dissolved, and then add pure water to the required volume.
3. The process for plating high-strength structural steel with a low-hydrogen embrittlement zinc-nickel alloy as described in claim 1, characterized in that: Cobalt particles are used as the anode. The cobalt particles are placed in a titanium anode basket and an anode bag is placed over the anode basket. The area ratio of the anode to the cathode is 4:(0.5~1.5).
4. The process for plating high-strength structural steel with a low-hydrogen embrittlement zinc-nickel alloy as described in claim 1, characterized in that: During production, solid potassium fluorotitanate is added to the plating solution to maintain its concentration within the range required by the process.
5. The process for plating high-strength structural steel with a low-hydrogen embrittlement zinc-nickel alloy as described in claim 1, characterized in that, The process composition and parameters for sulfuric acid anodic activation are as follows: Sulfuric acid concentration of 200–300 g / L, operation at room temperature, with the workpiece to be plated as the anode, and an anode current density of 0.6–1.2 A / dm³. 2 Electrolysis for 20–40 seconds.
6. The process for plating high-strength structural steel with a low-hydrogen embrittlement zinc-nickel alloy as described in claim 1, characterized in that, The zinc-nickel alloy plating process described above uses the Detronzin 1215 alkaline zinc-nickel alloy electroplating process: Zinc 5.5–8.5 g / L, Nickel 1.0–1.8 g / L, Sodium hydroxide 120–135 g / L, DETRONZIN 1215 Base additive 90–110 mL / L, DETRONZIN 1215 Brightener 1.0–5.0 mL / L, DETRONZIN 1215 Purifier R 0.1–0.8 mL / L, plating bath temperature 21–28℃, cathode current density 1.0–3.0 A / dm³ 2 The cathode moves at a speed of 4–6 m / min. Alternatively, the DETRONZIN 1377 acid zinc-nickel alloy electroplating process can be used: Zinc 22-30 g / L, Nickel 22-30 g / L, Potassium Chloride 160-190 g / L, Ammonium Chloride 45-75 g / L, DETRONZIN 1377ABase additive 10-20 mL / L, DETRONZIN 1377B Bri brightener 0.5-1.5 mL / L, DETRONZIN 1377C Complexing agent 10-20 mL / L, DETRONZIN 1377D Additive additive 8-12 mL / L, plating bath temperature 27-31℃, plating solution pH 4.6-5.2, cathode current density 0.5-3.5 A / dm³ 2 The cathode moves at a speed of 3–5 m / min.
7. The process for plating high-strength structural steel with a low-hydrogen embrittlement zinc-nickel alloy as described in claim 1, characterized in that, The hexavalent chromium passivation process described above uses the CB 380 hexavalent chromium color passivation process: CB 380 zinc-nickel hexavalent chromium colored passivating agent 80-100 mL / L, passivation solution pH 1.6-1.8, operating temperature 35-40℃, immersion time 60-80 s, workpiece oscillation.
8. Alternatively, the UUC 730 hexavalent chromium black passivation process may be used: UUC 730 A additive 120~160mL / L, UUC 730 B additive 120~160mL / L, passivation temperature 20~30℃, passivation solution pH 0.7~0.9, passivation time 60~120s, workpiece oscillation.
9. A high-strength structural steel low-hydrogen embrittlement zinc-nickel alloy coating structure, characterized in that: It includes a high-strength structural steel substrate, and a cobalt-titanium alloy coating, a zinc-nickel alloy coating, and a hexavalent chromium passivation film sequentially prepared on the high-strength structural steel substrate.
10. The high-strength structural steel low-hydrogen embrittlement zinc-nickel alloy coating structure as described in claim 8, characterized in that: The thickness of the cobalt-titanium alloy coating is 4–8 μm.
11. The high-strength structural steel low-hydrogen embrittlement zinc-nickel alloy coating structure as described in claim 8, characterized in that: The thickness of the zinc-nickel alloy coating is 5–20 μm.
Citation Information
Patent Citations
Cyanide-free cadmium-iron alloy plating process for high-strength structural steel
CN119980226A